Altered immunometabolism at the interface of increased endoplasmic reticulum (ER) stress in patients with type 2 diabetes. Issue 4 (29th June 2015) - Lenin, Raji; Sankaramoorthy, Aravind; Mohan, Viswanathan; Balasubramanyam, Muthuswamy
Abstract : The interconnectivity between decreased miR-146a levels and ER stress/proinflammation with therapeutic implications. Abstract: The mechanism of perturbed immune function in patients with T2DM is poorly understood. Recent studies imply a role for ER stress in linking immune-system alterations and metabolism. Here, we investigated whether ER stress markers and its downstream effector signals are altered in patients with type 2 diabetes along with proinflammatory augmentation. In our study, gene and protein expression of ER stress markers (GRP-78, PERK, IRE1α, ATF6, XBP-1 and CHOP) was elevated significantly ( P < 0.05) in PBMCs from T2DM patients compared with control subjects. The mRNA expression of both the proinflammatory cytokines (TNF-α and IL-6) and oxidative stress markers (p22 phox, TXNIP, and TRPC-6; P < 0.05) was also increased in PBMCs from patients with T2DM. SOCS3 mRNA expression was reduced significantly ( P < 0.05) in diabetes patients. mRNA expression of most of the ER stress markers from PBMCs correlated significantly and positively with poor glycemic control, dyslipidemia, IR, and inflammatory and oxidative stress markers. Chronic ER stress in PBMCs from patients with T2DM was evident from the increased caspase-3 activity ( P < 0.01), which is an executioner of apoptosis. Along with an impairment of miR-146a levels, the downstream targets of miR-146a, viz., IRAK1 and TRAF6 mRNA levels, were also elevated significantly ( P < 0.01) in patients with T2DM. There was an inverse relationship among miR-146a levels and ER stress markers, inflammatory markers, and glycemic control. We demonstrate evidence of increased ER stress markers with impaired miR-146a levels and increased proinflammatory signals in patients with type 2 diabetes.